Recommendation for treatment of hepatitis C virus infection - Kaymakoğlu, Sabahattin; Köksal, İftihar; Tabak, Fehmi; Akarca, Ulus S.; Akbulut, Ayhan; Akyüz, Filiz; Bodur, Hürrem; Çağatay, Atahan; Dinçer, Dinç; Esen, Şaban; Güner, Rahmet; Gürel, Selim; et al. (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Kaymakoğlu S, Köksal İ, Idilman R; Viral Hepatitis Guidelines Study Group. Recommendation for treatment of hepatitis C virus infection. Turk J Gastroenterol 2017; 28(Suppl 2); SX-SX.